Malignant Peripheral Nerve Sheath Tumors of the Head and Neck: A Case Series and Literature Review - Brandon T. Mullins; Trevor Hackman (Case Reports in Otolaryngology)
Background. Malignant peripheral nerve sheath tumors (MPNSTs) of the head and neck are rare aggressive neoplasms with a poor prognosis. This study describes the management and outcomes of 3 of our patients with MPNSTs of the head and neck. Methods. We identified 3 patients presenting with MPNST of the head and neck and treated at the University of North Carolina. We compared our results to the literature from 1963 to 2014. Results. Mean follow-up was 31 months. Average age at diagnosis was 44.7 years of age. All patients received wide-local excision and adjuvant radiotherapy. No patients recurred during the series. Recurrence-free survival time for the patients was 45, 37, and 3 months, respectively. Conclusions. Our data series confirms that a combined-modality approach with complete surgical resection and adjuvant radiotherapy leads to improved outcomes in MPNSTs of the head and neck. Nonetheless, due to historically poor outcomes, continued research into newer therapies needs to be explored.